Impact of supplemental phosphorus source and form on utilization in lactating dairy cattle - Lager, Kevin John (Kansas State University, 2009)
Supplemental phosphorus (P) in varying forms and sources: pellet (PELLET), meal (MEAL), liquid (LIQUID) and corn dried distiller’s grains with solubles (DDGS) were compared in twelve multiparous Holstein cows producing approximately 43 kg of milk (115 [plus minus] 55 DIM) in a 4x4 Latin square with 21d periods. PELLET and MEAL diets contained monocalcium phosphate with a wheat middlings carrier, and the LIQUID contained ammonium polyphosphate in a cane molasses base. The DDGS supplied an organic P source. Cows were blocked by parity, DIM and milk production and randomly assigned to treatments. Data were analyzed using the MIXED model procedure of SAS. Phosphorus intakes of 116, 116, 119 and 118 g/d were similar for PELLET, MEAL, LIQUID and DDGS diets, respectively. Cows consuming the LIQUID diet experienced greater sugar intakes (P<0.001). Fat intake was lower (P<0.001) for the PELLET, MEAL and LIQUID diets compared to the DDGS diet (1.14, 1.12, 1.07 and 1.36 kg/d, respectively). NEL intake was similar for all treatments (P=0.55). Milk yield differences (P=0.05) occurred with the DDGS diet yielding the most milk (34.6, 35.4, 34.1 and 36.5 kg/d). No differences resulted for either milk fat (P=0.26) or milk protein (P=0.33) percentages or for daily lactose production (P=0.22). Excretion of P in feces tended (P=0.07) to differ between treatments (67.4, 66.3, 57.5 and 60.0 g/d) resulting in a trend (P=0.10) for greater P retention in diets excreting less P. Secretion of P in milk did not differ (P=0.51) between treatments. Differences (P=0.04) occurred in P concentration between diets (0.47, 0.47, 0.49 and 0.47%), but the amount of P fed was not different (P=0.83). With similarities for DMI and P concentration in refusals (P=0.21) it may be deduced that sorting of the P supplement did not occur. These data show that supplemental P sources do not affect DMI or P intake, however P source resulted in slight differences in P utilization, but it was not related to sorting of the diet. Utilizing DDGS showed similar responses to inorganic P mineral supplements with favorable production yields making it an adequate substitute for mineral sources of P.
Keywords: Liquid feeds; Distillers grains; Milk production; Feed sorting; Milk composition; Feed pellets; Agriculture, Animal Culture and Nutrition (0475)